KNOWLEDGE AND USAGE PATTERN OF FOLIC ACID AMONG MEDICAL STUDENTS OF RAWALPINDI - ChaudhrI, Dr. Shahana; Kamran, Dr. Javeria; Atif, Dr. Rabia; Gillani, Dr. Rehma; Ihsan, Dr. Siddra; Shahid, Dr. Afshan; Inam, Dr. Hafsa (Pakistan Armed Forces Medical Journal, 2019)
Background: Neural Tube Defects (NTDs) are birth defects of brain and spinal cord that can result in permanent damage to the brain, resulting in lifelong disability or even death. The NTDs include spina bifida, anencephaly, hydrocephalus etc. NTDs affect 0.5-12 in every 1000 pregnancies worldwide.Objective:1. Assess knowledge regarding periconceptional use of folic acid among medical students.2. Toidentify the demographic and social factors that affects the knowledge of folic acid use in medical students.3. To find out the attitude of students and their practice regarding use of daily multivitamin supplements.Study Design: Cross sectional study.Place and Duration of Study: Rawal Medical and Dental College Islamabad, from Mar to Aug 2016.Material and Methods: Sample size of 154 was selected through simple random sampling. Structured questionnaire was used to collect data.Results: Total 154 final year medical students were included in the study. From all study participants, 38% (59) were male and 62% (95) were female. Residence distribution of 154 respondents was, 28 respondents were resident of rural setting while 126 were living in urban areas. Out of 154 study participants, 50 were boarder and 104 were non-boarder. Knowledge about folic acid was 43% (66). Association between folic acid use andknowledge was statistically significant.Conclusion: Higher proportion of respondents having good knowledge about folic acid intake was residing in urban areas while this is also not an important characteristic to be associated with knowledge of a person. Parental education also is not an important variable capable of influencing respondent’s knowledge or their practices.